PERAN IKLIM ORGANISASI TERHADAP WORK ENGAGEMENT DENGAN OPTIMISME SEBAGAI MEDIATOR - ARAS, REZKY ARIANY ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Work engagement has captured the attention of business practitioners, academic researchers and governments to understand the concept itself as well as its causes and consequences.Some researches indicate that work engagement is one of keys to perform best performances. Work engagement has been studied including the antecedents, which are job resources and personal resources. However only a few studies have demonstrated predictors and outcomes of work engagement on an ongoing basis. There are six areas of work life potentially provide a way to conceptualize the climate for engagement. When measured as the climate construct (at the level of unit or organization), six areas of work life (workload, control, reward, community, fairness, and values) can influence employee perceptions of job demands and job resources, which in turn affects work engagement. On the other hand optimism becomes more prominent and better predictor of the work engagement. This study aims to examine how the organizational climate (six areas of work life) influence work engagement and optimism as mediator. This research is a cross sectional study uses work engagement scale, organizational climate scale, and optimism scale for data collection. Subjects consisted of 61 employees of Psychology Faculty of Gadjah Mada University.Data is analysed by multiple linear regression analysis. Result shows optimism ism is partial mediator of organizational climates influence toward work engagement.